Social Entrepreneurship Intentions Among University Students: A Comparative Analysis Across Academic Disciplines (American Journal of Social Development and Entrepreneurship, 2025)
This study analyzes social entrepreneurship intentions among 201 university students from five academic programs: Business Psychology, Tourism Management, Media Design, Psychology, and Social Work. The findings show that Business Psychology students report the highest founding intentions (M = 4.2), driven by greater self-efficacy and risk readiness. In contrast, Social Work students display the lowest founding intentions (M = 3.1), despite high social motivation. These results suggest that academic background significantly influences entrepreneurial behavior. The study recommends tailored educational programs to enhance self-efficacy and risk readiness, especially in non-business fields, to promote social entrepreneurship across disciplines.